FACTORS INFLUENCING CONTRACEPTION METHODS IN TIAKUR PUBLIC HEALTH CENTERSOUTHWEST MALUKU REGENCY (Journal of Namibian Studies : History Politics Culture, 2023)
Long-Term Contraceptive Methods (MKJP) are very effective contraceptives, cover a long duration and work for up to 10 years. The Long Term Contraceptive Method (MKJP) has several types of contraception, namely Implants, IUDs, MOWs, and MOPs. Types of contraception in the Long-Term Contraceptive Method (MKJP) used for women of childbearing age are Implants, IUDs, and MOWs. One of the problems that need attention in the implementation of family planning programs is that there are PUS who discontinue contraceptive methods. This study aims to determine the determinants of the use of long-term contraceptive methods at the Tiakur Community Health Center, Southwest Maluku Regency. This type of research is quantitative research. The research sample is 100 respondents. Samples were taken from all active acceptors at the Tiakur Public Health Center. Sampling was done using a simple random sampling technique. The data analysis used was univariate, bivariate analysis using the Chi-Square formula. The results of the chi-square test showed that there was a relationship between education level (p=0.004), income (p=0.000), and the use of MKJP at the Tiakur Health Center, Southwest Maluku Regency. Furthermore, there was no relationship between access to service points (p=0.101) and the use of MKJP at the Tiakur Health Center, Southwest Maluku Regency. Suggestions for the Puskesmas are increasing counseling, information, and education activities for the community through leaflets or audio-visual so that acceptors are more interested in using MKJP.